Memory B cells and their transcriptomic profiles associated with belimumab resistance in systemic lupus erythematosus in the maintenance phase - Iwasaki, Takeshi; Yoshifuji, Hajime; Kitagori, Koji; Sumitomo, Shuji; Akizuki, Shuji; Nakashima, Ran; Tsuji, Hideaki; Hiwa, Ryosuke; Shirakashi, Mirei; Murakami, Kosaku; Onishi, Akira; Onizawa, Hideo; et al. (Frontiers in Immunology, 2025)
The factors contributing to the treatment efficacy of belimumab in patients with systemic lupus erythematosus (SLE) in the maintenance phase are unknown. Here, we collected blood samples from patients with SLE (n=44) treated with belimumab before and three and six months after treatment. RNA-Seq of whole blood was performed, and gene expression was quantified. Immune cell type enrichment analysis estimated immune cell subtype proportions and gene expression in each subtype. The Systemic Lupus Erythematosus Disease Activity Index 2000 (SLEDAI-2K) < 4 at six months was set as the primary efficacy criterion. Non-responders exhibited upregulated B cell proliferation signals before treatment, associated with an increased number of memory B cells. A higher proportion of memory B cells before treatment predicted poor response (p=5.1×10-4). This was also associated with changes in disease activity and glucocorticoid dose at six months compared with baseline. Belimumab did not affect memory B cell proportion during the treatment time course, in contrast to naïve B cells. Higher memory B cell proportion was associated with higher type-I interferon (IFN) scores and lower white blood cell and complement C4 levels. Transcriptomic analysis of memory B cells in non-responders revealed significant upregulation of immunoglobulin genes (Ig). Memory B cells and high Ig expression in them were identified as a treatment-resistant factor of belimumab in SLE patients. Lower C4 and white blood cell counts may serve as clinical markers of higher memory B cells.